1996
DOI: 10.2134/jeq1996.00472425002500040014x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Removal in Stream Riparian Zones

Abstract: This review considers the role of stream riparian zones in regulating the transport of nitrate (NO−3) in groundwater flow from uplands to streams. The current consensus is that most riparian zones effectively remove NO−3 from subsurface water. However, research has not focused on the relationship between hydrology and chemistry within the context of the riparian zone hydrogeologic setting. Most riparian zones that remove NO−3 occur in landscapes with impermeable layers near the ground surface. In this setting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
596
3
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 793 publications
(625 citation statements)
references
References 0 publications
20
596
3
6
Order By: Relevance
“…The elevated rates we observed reflect environmental conditions conducive to denitrification, i.e. low DO (<1 mg O 2 /L; Table 3) plus a highly enriched organic matter sediment (Table 2) and optimum sediment-water contact time within the confined lysimeter environment (Hill 1996;Fennessy and Cronk 1997;Hoffmann et al 2000;Smith et al 2003). The observed high denitrification rates could be attributed to the elevated DEA values (Table 4) in the wetland soils (Groffman et al 1999).…”
Section: Preliminary Testing Of the Push-pull Technique Within A Confmentioning
confidence: 64%
See 1 more Smart Citation
“…The elevated rates we observed reflect environmental conditions conducive to denitrification, i.e. low DO (<1 mg O 2 /L; Table 3) plus a highly enriched organic matter sediment (Table 2) and optimum sediment-water contact time within the confined lysimeter environment (Hill 1996;Fennessy and Cronk 1997;Hoffmann et al 2000;Smith et al 2003). The observed high denitrification rates could be attributed to the elevated DEA values (Table 4) in the wetland soils (Groffman et al 1999).…”
Section: Preliminary Testing Of the Push-pull Technique Within A Confmentioning
confidence: 64%
“…The low level of NO 3 À in wetland waters (Table 3) suggests that any NO 3 À that enters the wetland via seepage springs and runoff is readily removed by denitrification (Zaman et al 2008b) and other biological processes (Seitzinger 1994;Hill 1996;Fennessy and Cronk 1997;Matheson et al 2002Matheson et al , 2003. Ammonium and organic N were the predominant N fractions in both surface and subsurface waters (Table 3), likely due to inputs from farmland runoff and/or the incomplete breakdown of organic matter originating from wetland organic sediments and/or plant vegetation under anaerobic conditions (Nguyen 2000).…”
Section: Wetland Sediment Physical and Chemical Characteristics And Pmentioning
confidence: 99%
“…Only 33% of the apparent nitrate uptake could be explained by tree growth (Peterjohn and Correll, 1984), suggesting that much of the intercepted nitrogen may be consumed by denitrification. Although many studies have suggested that riparian forests may be important sinks for N, the mechanisms of N uptake are not well understood (Hill, 1996).…”
Section: Importance Of Denitrificationmentioning
confidence: 99%
“…Much of the N released from agricultural lands can be intercepted by adjacent downhill riparian forests (Lowrance et a/., 1984;Osborne and Kovacic, 1993;Hill, 1996: Correll, 1997. The effectiveness of riparian forests as N sinks may strongly influence watershed discharges of N (Jordan et ul., 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation